Pemanfaatan Teknologi Digital dalam Pelayanan Kesehatan Publik: Sebuah Tinjauan Analisis Kebijakan - Ramadhany Nugroho; Muhamad Hidayat; Emilia Devi Dwi Rianti; Ni Luh Ayu Citra Mutiarahati; Achmad Fathor Rosyid (Jurusan Administrasi Publik FISIP UIN SGD Bandung, 2023)
The use of digital technology in health services has become a significant trend in recent years. The use of technology in public health services is strongly influenced by various government policies. This research was carried out with the aim of reviewing government policies in the use of digital technology in public health services. The method used in this research is a qualitative method through literature study. The results of this study then found that the use of digital technology had a positive impact in increasing the accessibility, efficiency and accuracy of health services. Government policies play an important role in encouraging and regulating the use of digital technology in health care. However, challenges in implementation cannot be ignored. Availability of adequate infrastructure and internet connection, concerns regarding patient data privacy and security, and lack of understanding and technological skills are obstacles that need to be overcome. Collaboration between the government, health institutions and other stakeholders is an important key in overcoming these challenges.